การพัฒนาสายพันธุ์และการทดสอบพันธุ์ลูกผสมข้าวโพดข้าวเหนียวเบื้องต้นที่มีศักยภาพผลผลิตสูงในจังหวัดพะเยาโดยวิธีสายพันธุ์ผสมกับตัวทดสอบ - Sinkangam, Bunyarit; Chunvijit, Pavinee (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 2 (2014): May-August 2014, 2014)
การปรับปรุงพันธุ์ข้าวโพดข้าวเหนียวในโครงการปรับปรุงพันธุ์ข้าวโพดมหาวิทยาลัยพะเยา (UPMI) โดยวิธีการ S1 selection จานวน 90 สายพันธุ์ คัดเลือกสายพันธุ์ที่มีลักษณะทางเกษตรที่ดีในประชากรผสมตัวเองชั่วที่ 3 จานวน 10 สายพันธุ์ (UP004-1, UP010-1, UP021-1, UP022-1, UP026-2, UP029-2, UP033-1, UP042-1, UP043-2 และ UP044-1) พบว่า มีอะมิโล เพคตินมากกว่า 95% ทั้งเมล็ดสดและแห้ง มีปริมาณน้าตาลทั้งหมดตั้งแต่ 58.3-88.3 และ non-reducing ตั้งแต่ 15.0-51.5 mg/g ขณะที่ผลผลิตทั้งเปลือก, ผลผลิตปอกเปลือก, shelling และ การตัดฝาน พบว่า สายพันธุ์ที่สูงที่สุด คือ UP044-1 (1,275 กก/ไร่), UP010-1 (734 กก/ไร่), UP022-1 (73.5%) และ UP022-1 (57.3%) ตามลาดับ ประเมินสายพันธุ์สร้างลูกผสมโดยผสมตัวทดสอบ 3 ตัว ได้แก่ UPWC1, 3 และ 6 ในฤดูปลายฝน 2013 และทดสอบผลผลิตฤดูแล้ง 2013 ได้ลูกผสม 30 คู่ผสม พบว่า มีอะมิโลเพคติน 94-97% (เมล็ดสด) และ 95-97% (เมล็ดแห้ง) total sugar 53.1-90.9 และ reducing sugar 14.0-54.6 mg/g วันออกดอกตัวผู้และตัวเมีย พบว่า อยู่ในช่วง 43-50 และ 43-48 วัน ตามลาดับ ผลผลิตทั้งเปลือกและปอกเปลือกดีที่สุด คือ UP021-1 x UPWC3 (2,127 กก/ไร่) และ UP033-1 x UPWC1 (1,523 กก/ไร่) คู่ผสมที่มี shelling และการตัดฝานสูงที่สุด คือ UP029-2 x UPWC1 เท่ากับ 89.6% และ UP044-1 x UPWC6 เท่ากับ 62.9% ตามลาดับ สาหรับความหนาบางของ pericarp ทั้งด้าน germinal และ abgerminal พบว่า คู่ผสมที่บางที่สุด คือ UP021-1 x UPWC1 เท่ากับ 152.3 และ 135.9 ไมครอน ขณะที่คุณภาพในการกัดชิม ได้แก่ ความชอบ, ความนุ่ม และความหนา pericarp พบว่า คู่ผสมที่มีคะแนนดีที่สุด คือ UP010-1 x UPWC1 (4.1), UP029-2 x UPWC6 (4.3) และ UP010-1 x UPWC1 (1.5) คำสำคัญ: ตัวทดสอบ ข้าวโพดข้าวเหนียว ลูกผสม         The University of Phayao Maize Improvement (UPMI) has strongly emphasized performing the waxy corn improvement. Namely, ninety accessions were collected and initiated by simply S1 selection model. Then, ten lines of S3 generation were selected that many agronomic characters and adaptation were good, viz, UP004-1, UP010-1, UP021-1, UP022-1, UP026-2, UP029-2, UP033-1, UP042-1, UP043-2 and UP044-1. Data recording, the amylopectin content of both kernels (fresh and dry) was approximately 95%. Sugar content, total averaged 58.3-88.3 mg/g and non-reducing was 15.0-51.5 mg/g. Moreover, yield components were performed, viz, green weight, white weight, shelling and cutting. The results showed that the best line was UP044-1 (1,275 kg/rai), UP010-1 (734 kg/rai), UP022-1 (73.5%) and UP022-1 (57.3%), respectively. The preliminary F1 hybrid establishment, there were crossed by three testers, UPWC1, 3 and 6, operated in late rainy season 2013. Yield trial evaluation, thirty crosses were received and conducted in dry season 2013. Many agronomic characters were recorded. Namely, amylopectin content ranged 94-97% of both kernels. Furthermore, total and non-reducing sugar were 53.1-90.9 and 14.0-54.6 mg/g, respectively. Day to flowerings, tasseling and silking were 43-50 and 43-48 days, respectively. Most importantly, the best crosses of green and white weight were UP021-1 x UPWC3 (2,127 kg/rai) and UP033-1 x UPWC1 (1,523 kg/rai), respectively. Shelling and cutting percentage found that in UP029-2 38 x UPWC1(89.6%) and UP044-1 x UPWC6 (62.9%). In addition, the pericarp thickness measured two sides, germinal and abgerminal. The results revealed that the thinnest line was UP021l-1 x UPWC1 equal to 152.3 and 135.9 micron, respectively. The eating qualities consisted of flavor, tenderness and pericarp thickness were scored. The best crosses of eating qualities, there were UP010-1 x UPWC1 (4.1), UP029-2 x UPWC6 (4.3) and UP010-1 x UPWC1 (1.5). Keywords: tester, waxy corn, F1 hybrid
Keywords: ตัวทดสอบ ข้าวโพดข้าวเหนียว ลูกผสม tester, waxy corn, F1 hybrid